Direct Metal‐Free Preparation of Functionalizable Polylactic Acid‐Ethisterone Conjugates in a One‐Pot Approach. Issue 5 (18th January 2019) - Luo, Shi‐He; Wu, Yan‐Cheng; Cao, Liang; Lin, Jian‐Yun; Gao, Jian; Chen, Shui‐Xia; Wang, Zhao‐Yang
Abstract: A series of polylactic acid (PLA) conjugates (PLA‐ES) are synthesized via direct melt polycondensation (DMP) of lactic acid (LA) with ethisterone (ES) in the presence of 0.3 wt% toluenesulfonic acid at 160 °C for 6 h. The drug content of PLA conjugates can be simply adjustable. Further functionalization via Click chemistry is also achieved to extend the biomedicine application of biopolymer based drug delivery. Abstract : A method for merging polymeric carrier preparation and chemical conjugation into one‐pot, via solvent‐ and metal‐free direct melt polycondensation, for functionalizable polylactic acid‐ethisterone (PLA‐ES) conjugates is developed.